Hubungan Karakteristik Responden Terhadap Perilaku Bullying Pada Remaja - Rahayu, Wisha Listya; Wati, Del Fatma (REAL in Nursing Journal, 2024)
Background: individual or group. According to the International Center for Research on Women (ICRW), 84% of Indonesian children experience bullying in schools. Despite the prevalence, there is a lack of specific research investigating the relationship between respondent characteristics and bullying behavior among adolescents. This study aims to explore the association between respondent characteristics and bullying behavior among students at SMPN 8 Bukittinggi in 2023. Methods: This quantitative study employs an analytical descriptive approach with a cross-sectional design conducted in October 2023, involving a population of 491 students. Sample selection utilized purposive sampling, resulting in 83 respondents. Data collection was performed through questionnaires, and data analysis included univariate and bivariate analyses. Results: Findings reveal that out of 38 male respondents, 23 (60.5%) engaged in bullying while 15 (39.5%) did not. Regarding siblings, out of 80 respondents with more than one sibling, 38 (47.5%) engaged in bullying compared to 42 (52.5%) who did not. Among 82 adolescents from middle-income families, 38 (46.3%) were involved in bullying while 44 (53.7%) were not. Gender exhibited a significant association with bullying behavior (P value = 0.040 ≤ α), whereas no significant relationships were found between the number of siblings (P value = 1.000 > α) or economic status (P value = 0.470 > α) and bullying behavior. Conclusion: Hence, it is recommended for schools to enhance education and counseling efforts concerning bullying.